(untitled) (Confluenţe Bibliologice, 2024)
The article contains information on the history of Bessarabia. Historical data are highlighted regarding the loss of Bessarabia in 1812, the struggle between the great powers, the Russian-Turkish peace treaty of May 28, 1812, the negotiations between the representatives of the Ottoman Empire and the Russian Empire, the establishment of the border on the Prut. Why did the Romanian diplomat Titulescu consider the Russian-Turkish treaty of 1812 null and void.